Study of Cryptography in Cloud Computing (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
If all of the top levels of security fail, the final and most critical tier, data security, must not fail. By breaching this layer of defence, the CIA's triad principles of confidentiality, integrity, and availability are undermined. However, increasing security reduces the performance of the system and usability. This paper addresses the fundamentals of cloud computing as well as its key challenge: security. This paperexamines a variety of cryptographic methods used by major cloud providers. It proposes an alternative algorithm for encrypting data in transit from the user to the cloud in order to ensure data security and defend against Man-in-the- Middle (MitM) attacks like sniffing. The paper concludes by urging further study into the proposed cryptography algorithm in order to ensure data protection and privacy in all three data states.